Pemberdayaan Masyarakat Dalam Pemanfaatan Obat Tradisional - Sri Suwarni; Atalia Ina Bulu; Agustina Ratna Wulandari; Pertiwi Setyaningrum (Universitas Pahlawan Tuanku Tambusai, 2022)
Health as one of the basic human needs has a strategic role for efforts to improve human welfare. Health problems can be suppressed using traditional medicine. The purpose of educating the public to use traditional medicine.The method in this activity is socialization by using Counseling and Demonstration of the Use of the SiJAhe Application (Herbs and Herbal Information System) with an analysis of changes in the level of knowledge of the Kaligawe Village community with 51 participants with a place at the Semarang City Health Office on 27 March 2021 at 09.00 WIB until 12.0 WIB. Results The implementation of this community service activity was carried out well and smoothly from the initial preparation to the end and the community was very enthusiastic about the activity. The conclusion is that the community gains direct knowledge for the use of traditional medicine.